Non-traditional religious movements in modern Kazakhstani society (Eurasian Journal of Religious Studies, 2019)
This article discusses the process of development of non-traditional religious movements operating in modern Kazakhstan society. In addition, the main problems close to the concepts of non-traditional religious movement, giving the definition of the concepts of “sect”, “cult” were identified.  And also, among the non-traditional religious associations, which have recently considered Christianity, able to strengthen its role in Kazakhstan's public sphere are Jehovah's witnesses, “New life”, “grace-Grace”, “Church of Scientology” and others. in Addition, the article discusses the methods and techniques of functioning of religious movements and communities, the features of the Law of the Republic of Kazakhstan "On religious activities and religious associations". In the era of globalization, there is a dynamic growth of missionary activity, which is one of the features of non-traditional religious movements.In addition, the article reveals the General features characteristic of non-traditional religious movements operating in the country. Protestant denominations and charismatic movements and movements in Kazakhstan, as well as “Bahai community”, “Church Association”, “Church of the Last Testament”, “Church of Scientology”, “Church of unification”, etc. b. non-traditional destructive religious organizations are taken into account and analyzed as new structures.
Keywords: religion; non-traditional religious movements; Church; Protestantism; New Life; grace; Church of Scientology; Jehovah's Witnesses